Giải bài 4 trang 17 SBT Toán 8 tập 1 CTST
Bài 4 trang 17 SBT Toán 8 tập 1 CTST: Phân tích các đa thức sau thành nhân tử:
a)$ x^{3} – 1 000$;
b) $8x^{3} + (x – y)^{3}$;
c) $(x – 1)^{3} – 27$;
d) $x^{6} + y^{9}$.
a) $x^{3} – 1 000$
= $x^{3}‒ 10^{3}$
= $(x ‒ 10)(x^{2} + 10x + 10^{2})$
= $(x ‒ 10)(x^{2} + 10x + 100)$.
b) $8x^{3} + (x – y)^{3}$
= $(2x)^{3} + (x – y)^{3}$
= $(2x + x ‒ y)[(2x)^{2} ‒ 2x(x ‒ y) + (x ‒ y)^{2}]$
= $(3x ‒ y)(4x^{2} ‒ 2x^{2} + 2xy + x^{2} ‒ 2xy + y^{2})$
= $(3x ‒ y)[(4x^{2} ‒ 2x^{2} + x^{2}) + (2xy ‒ 2xy) + y^{2}]$
= $(3x ‒ y)(3x^{2} + y^{2}).$
c) $(x – 1)^{3} – 27$
= $(x – 1)^{3} – 3^{3}$
= $(x ‒ 1 ‒ 3)[(x ‒ 1)^{2} + (x ‒ 1).3 + 3^{2}]$
= $(x ‒ 4)(x^{2} ‒ 2x + 1 + 3x ‒ 3 + 9)$
= $(x ‒ 4)[x^{2} + (‒2x + 3x) + 1 ‒ 3 + 9]$
= $(x ‒ 4)(x^{2} + x +7).$
d) $x^{6} + y^{9}$
= $(x^{2})^{3} + (y^{3})^{3}$
= $(x^{2} + y^{3})[(x^{2})^{2} ‒ x^{2}.y^{3} + (y^{3})^{2}]$
= $(x^{2} + y^{3})(x^{4} ‒ x^{2}y^{3} + y^{6}).$
Bình luận